Adapting Victorian Gypsies for the Screen: Ethnicity, Otherness and (In)visibility in Neo-Victorian Popular Film - Martín-González, Juan José (My University, 2016)
This paper aims at analysing the presence of gypsy characters in two neo-Victorian popular films, namely Joe Johnston’s The Wolfman (2010) and Guy Ritchie’s Sherlock Holmes: Game of Shadows (2011). The cultural construction of nineteenth-century gypsies, those “Others within Europe” (Boyarin 433) whose presence in Victorian fiction was peripheral, spectral and at times invisible (Nord 3-4), is simultaneously exploited and contested by these two neo-Victorian screen narratives to raise issues of otherness and invisibility on the screen. Setting off from the premise that screen texts, just like print texts, can also be participant in the neo-Victorian project of reimagining the underside of Victorian culture for contemporary audiences (Whelehan 273), this paper traces how the adaptation of Victorian gypsies for the screen, true to the palimpsestuous potential inherent to the process of adaptation (Hutcheon 6) and sharing the double drive between past and present which characterises the neo-Victorian genre (Arias and Pulham xiii; Shiller 539), hybridises our cultural memory of the Victorian Age on the screen while concurrently raises concerns over the persistent liminal status of gypsies in contemporary European culture. In particular, this paper illustrates how the tropes prototypically associated to gypsies (namely their nomadic lifestyle, mysticism, alienated existence or their perceived association to criminality) which can be traced back to Victorian culture are deployed on the neo-Victorian popular screen (with varyingly succesful outcomes) to comment on their (in)visibility in the European popular imagination.
Keywords: Novela inglesa - S. XIX - Adaptaciones cinematográficas; Neo-Victorianism; Adaptation; Gypsies